A STUDY ON RECOVERY OF NON-PERFORMING ASSETS OF SCHEDULED COMMERCIAL BANKS IN INDIA - N. Arunsankar; R Santhoshkumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Non- Performing Assets is an important tool to judge the degree of the financial strength of any bank because it directly affects the profitability and financial efficiency of the banks. It is worthwhile at this stage to discuss the various recovery measures adopted by banks and financial institutions (FIs) for reducing the level of NPAs. Broadly speaking, recovery measures can be classified into Non-Legal and Legal measures. This research paper examines the recovery of Non – Performing Assets by scheduled commercial banks in India from various measures. The following are the objectives of the present paper that are framed to study the recovery of NPA in India: 1. To evaluate the Recovery procedure of Banks through various measures. 2.To examine the Recovery of NPA by banks under SARFAESI Act. For data analysis, AGR, Mean, SD, CV, GAGR, and ANOVA are used as statistical tools. Finally, this paper brings out the significant difference in the mean NPA recovery channels among scheduled commercial banks during the study period